Digital Taxes on Global Tech Companies and Interstate Tensions in the Digital Economy - Nurwanah, Andi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the impact of Digital Services Taxes (DSTs) on multinational tech companies and explores the geopolitical tensions arising from fragmented digital tax policies. It aims to assess how DSTs influence corporate strategies and contribute to regulatory and economic challenges in the global digital economy. Research Design and Methodology: A qualitative systematic literature review (SLR) was employed to analyze secondary data from peer-reviewed articles, policy documents, and international frameworks. The study integrates corporate strategy, international relations, and tax governance perspectives to understand DSTs' complexities comprehensively. Findings and Discussion: The findings reveal that DSTs significantly affect investment allocation, operational efficiency, and pricing strategies of multinational tech firms. Increased compliance costs and risks of double taxation challenge profitability and global competitiveness. Geopolitical tensions between countries implementing DSTs and those opposing them highlight the need for collaborative international tax reforms. The OECD’s Two-Pillar Plan emerges as a critical framework to address regulatory fragmentation and foster fiscal equity. The discussion underscores the role of stakeholder theory in bridging conflicting interests among governments, corporations, and societies to create sustainable solutions for digital taxation. Implications: This study highlights the importance of multilateral approaches to digital taxation and collaboration between policymakers and tech companies. Practical implications include developing transparent and inclusive tax frameworks that support innovation and global economic stability. For managers, adopting proactive compliance strategies and engaging in policy reforms are essential to navigate the challenges DSTs pose.